Thresholds are everywhere: A systems approach to public policy - Carvalho, Hamilton Coimbra; Isabella, Giuliana; Mazzon, José Afonso (Brazilian Administration Review, 2019)
The analysis of public policies often fails to account for effects beyond mere cost-benefit analysis. Incorporating elements from the literature on system dynamics, complexity and legitimacy, the present paper develops a framework to understand long-term effects and important constraints for public policies. We call it the thresholds framework, considering the existence of different thresholds in the life of a policy. The framework relies on the application of conceptual lenses to understand essential aspects of the social reality. Using the proposed conceptual repertoire, the paper applies the framework to a specific policy, the Brazilian Worker Food Program (WFP), which currently benefits around 20 million employees working for 250,000 companies in Brazil. The thresholds framework incorporates legitimacy and complexity issues and it is sufficiently flexible for the pursuit of different strategies of inquiry. It may be used to guide the design of business programs in dynamic contexts, such as the ones found in modern social cause environments.